Management of Urban Parks and Playgrounds in Developıng Countrıes: A Case Study - S. Kameswar Rao (International Journal of Advanced Science and Technology, 2020)
Urban areas are engines for economic augmentation and health in urban areas is attracting more attention across the globe. The rapid growth of urban population particularly in developing countries is due to natural growth and migration. The high growth of urban population obscures the state of basic amenities and transform into poor health status. The changes in urban lifestyle is ensuing in sedentary type of recreation like watching television, smart phones and working on computer. The main reason for health issues like obesity and diabetes is the changed urban lifestyle.  Urban parks and playgrounds can provide a large variety of opportunities to the community to develop skills and strengths needed to have a rewarding life. High growth of population and difficulty in revenue generation for creation of new and maintenance of existing parks and playgrounds are the major challenges especially in developing nations. The current study aims to evaluate the public opinion on parks and playgrounds provided by the Greater Visakhapatnam Municipal Corporation.Keywords: Parks & Playgrounds, Urban Areas, Average Life Expectancy (ALE)